The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/w12020443
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Field-Scale Phosphorus Removal Structures Utilizing Steel Slag for Treatment of Subsurface Drainage

Abstract: Reducing dissolved phosphorus (P) losses from legacy P soils to surface waters is necessary for preventing algal blooms. Phosphorus removal structures containing steel slag have shown success in treating surface runoff for dissolved P, but little is known about treating subsurface (tile) drainage. A ditch-style and subsurface P removal structure were constructed using steel slag in a bottom-up flow design for treating tile drainage. Nearly 97% of P was delivered during precipitation-induced flow events (as opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…The slag used in this study did not clog up, continues to remove dissolved P after three years, and performed as expected based on laboratory flow-through experiments, unlike the slag P removal structure reported by Penn et al [31]. The main difference in those studies is the source water; this study treated surface runoff water instead of tile drainage water, which contains appreciable bicarbonate and dissolved forms of CO 2 compared to surface runoff [31]. The under-performance of slag in their study was attributed to the formation of Ca carbonate instead of Ca phosphate through bicarbonate input, which additionally clogged the structure, besides consuming soluble Ca that would usually precipitate Ca phosphate for P removal.…”
Section: Summary and Implicationssupporting
confidence: 61%
See 2 more Smart Citations
“…The slag used in this study did not clog up, continues to remove dissolved P after three years, and performed as expected based on laboratory flow-through experiments, unlike the slag P removal structure reported by Penn et al [31]. The main difference in those studies is the source water; this study treated surface runoff water instead of tile drainage water, which contains appreciable bicarbonate and dissolved forms of CO 2 compared to surface runoff [31]. The under-performance of slag in their study was attributed to the formation of Ca carbonate instead of Ca phosphate through bicarbonate input, which additionally clogged the structure, besides consuming soluble Ca that would usually precipitate Ca phosphate for P removal.…”
Section: Summary and Implicationssupporting
confidence: 61%
“…While limestone-based blind inlets have been shown to remove little to no dissolved P [4,5], this study demonstrated that a simple update to slag would permit blind inlets to remove dissolved P in addition to sediment, particulate P, and provide obstruction-free drainage of depressions. The slag used in this study did not clog up, continues to remove dissolved P after three years, and performed as expected based on laboratory flow-through experiments, unlike the slag P removal structure reported by Penn et al [31]. The main difference in those studies is the source water; this study treated surface runoff water instead of tile drainage water, which contains appreciable bicarbonate and dissolved forms of CO 2 compared to surface runoff [31].…”
Section: Summary and Implicationsmentioning
confidence: 58%
See 1 more Smart Citation
“…29 The efficiency of steel slag in removing P from different types of water, surface water as well as wastewater, has been confirmed in the literature. [30][31][32] However, the present study contributes to the literature by explaining the role of aeration at different pH values in enhancing the removal mechanisms.…”
mentioning
confidence: 85%
“…Calcium carbonates precipitate on the slag instead of calcium phosphate when bicarbonate and dissolved forms of CO 2 are present in the subsurface drainage, which results from water infiltrating through calcareous soils and microbial respiration [ 41 , 42 ]. This decrease in capacity is due to (1) the bicarbonate and phosphate ions competing to adsorb to the calcium minerals and (2) the decrease in pH due to the formation of calcium carbonate and soluble calcium concentration, which negatively impacts the SFS’s ability to precipitate phosphate ions as calcium phosphate [ 41 , 42 ]. Specifically, the SFS has a decrease in P removal via calcium phosphate precipitation when the pH of the solution is below 8.5 [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%